Precursors of the neurosteroids. - Prasad, V V (1994)
In addition to the neurosteroids pregnenolone and dehydroepiandrosterone, organic solvent extracts of rat brains contain related compounds that react with various reagents to yield additional amounts of these ketosteroids. Among the chemicals producing these increments are triethylamine, HCl, FeCl3, and Pb(OAc)4. Most revealing is the action of FeSO4 on these extracts. This reducing agent also converts components of the extract into the two neurosteroids, suggesting the presence of sterol hydroperoxides or peroxides in brain. The clues provided by this study indicate that the chemical nature of the steroidal constituents existing in extracts of mammalian brains remains to be determined. It is likely that their association with neurological functions will be better understood when the structures of these substances are established.